2017
DOI: 10.7150/jca.21118
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 is a Prognostic Biomarker in Resected NSCLC Patients with Moderate/high Smoking History and Elevated Serum SCCA Level

Abstract: Programmed cell death-1 (PD-1) -targeted immunotherapy has become a promising treatment paradigm for patients with advanced non-small cell lung cancer (NSCLC). Clinical responses to checkpoint inhibition therapy in NSCLC have been associated with programmed death-1 ligand 1 (PD-L1) expression. However, the association between the expression of PD-L1 and PD-L2 and the clinicopathological features and patient outcomes in NSCLC remain unclear. We retrospectively analyzed 364 patients (158 squamous cell carcinoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…SCC‐Ag showed to be valuable as a prognostic serum tumor marker in cervical cancer and non‐small‐cell lung carcinoma, but not so in HNSCC . Because the diagnostic value of SCC‐Ag in FNA is a new finding, it would be of interest to see whether the SCC‐Ag concentration has any prognostic value.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SCC‐Ag showed to be valuable as a prognostic serum tumor marker in cervical cancer and non‐small‐cell lung carcinoma, but not so in HNSCC . Because the diagnostic value of SCC‐Ag in FNA is a new finding, it would be of interest to see whether the SCC‐Ag concentration has any prognostic value.…”
Section: Discussionmentioning
confidence: 99%
“…The measurement of squamous cell carcinoma antigen (SCC‐Ag), originally purified from SCC of the human uterine cervix, could improve the detection of regional HNSCC lymph node metastases in addition to FNAC. Although SCC‐Ag is used as a prognostic serum tumor marker in cervical cancer and non‐small‐cell lung cancer, in HNSCC, the serum SCC‐Ag level showed no significant relation to lymph node metastasis and overall survival . To our knowledge, SCC‐Ag in FNA samples has not previously been studied.…”
Section: Introductionmentioning
confidence: 91%
“…DFS and OS were stratified by median of NLR (2.3), which was also consisting with previous studies [15][16][17][18] . Epidermal growth factor receptor (EGFR) mutation status was detected by real-time PCR or DNA sequencing as previously described [19].…”
Section: Patientsmentioning
confidence: 99%
“…Although the association between PD-L1 expression and clinicopathological characteristics in NSCLC has already been examined, the relationship between oncogenic driver mutations, smoking history, and PD-L1 expression status remains unclear. Recent studies have demonstrated that high PD-L1expression is more frequently found in resected NSCLC patients with a smoking history, [9][10][11] while other studies have found no relationship. 12 Furthermore, detailed analysis of the association between PD-L1 expression and smoking variables was not performed in these studies.…”
Section: Introductionmentioning
confidence: 96%